Assessing business management factors in young agricultural entrepreneurs in Indonesia - Kansrini , Yuliana; Lubis, Zulkarnain; Effendi, Ihsan; Mulyani, Puji Wahyu; Apriliani, Anggi (Universitas Lancang Kuning, 2024)
Indonesia faces a pressing challenge in its agricultural sector: the declining participation of young workers due to limited entrepreneurial opportunities and inadequate business management skills. This study investigates the factors influencing business management among young agricultural entrepreneurs participating in the growth of young agricultural entrepreneurs (PWMP) program at Politeknik Pembangunan Pertanian (Polbangtan) Medan, Indonesia. Utilizing a descriptive quantitative approach, data were gathered through questionnaires and analyzed using Likert scale measurements and multiple linear regression tests. The findings highlight that business management capabilities were categorized as high (79.68%), supported by strong personality traits (84.30%), high knowledge levels (83.05%), extensive experience (81.13%), a supportive family environment (75.80%), and a robust entrepreneurial ecosystem (79.78%). Regression analysis revealed that personality, experience, family environment, and the entrepreneurial ecosystem significantly impacted business management capabilities, while knowledge had no notable effect. These results underscore the importance of structured interventions, such as internships and business incubation programs, to enhance practical business skills and foster entrepreneurial success.